2022
DOI: 10.1021/acs.inorgchem.2c04000
|View full text |Cite
|
Sign up to set email alerts
|

Near-Infrared-Induced Photothermal Enhanced Photocatalytic H2 Production for 3D/2D Heterojunctions of Snowflake-like CuS/g-C3N4 Nanosheets

Abstract: The conversion of solar power to hydrogen (H 2 ) energy efficiently encounters some obstacles due to the lack of superior catalysts and efficient catalytic approaches. Herein, three-dimensional/ two-dimensional (3D/2D) CuS/g-C 3 N 4 photothermal catalysts were obtained via an easy, one-step hydrothermal method after pyrolysis. The favorable heterojunction interface for H 2 production was constructed by snowflake-like CuS embedded in the graphite carbon nitride (g-C 3 N 4 ) nanosheets, leading to the accelerati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 56 publications
1
6
0
Order By: Relevance
“…33 The strong interfacial interaction reduces charge movement distance, accelerates the charge transfer rate, boosts free radical generation, and improves the catalytic degradation of MO. [34][35][36][37] It is also consistent with the XRD results.…”
Section: Catalyst Characterizationsupporting
confidence: 90%
“…33 The strong interfacial interaction reduces charge movement distance, accelerates the charge transfer rate, boosts free radical generation, and improves the catalytic degradation of MO. [34][35][36][37] It is also consistent with the XRD results.…”
Section: Catalyst Characterizationsupporting
confidence: 90%
“…We have performed photoelectrochemical measurements to examine the separation and transfer capability of photogenic carriers as shown in panels a and b of Figure . The MCN 2:1 photocatalyst displayed a higher photocurrent and a smaller electrochemical impedance with and without illumination compared to those of the pure CN sample, demonstrating that the construction of 2D/2D MXene/CN could conspicuously restrict the recombination of photogenerated electron–hole pairs and expedite the charge transfer along the 2D interface . The photoluminescence spectroscopy (PL) characterization further corroborated the results mentioned above because the peak intensity of MCN at 450 nm was significantly lower than that of CN (Figure c).…”
Section: Resultsmentioning
confidence: 98%
“…A CuS/g-C 3 N 4 with a compact heterojunction structure was fabricated, resulting in the preferable realization of converting NIR light into heat and acceleration of charge transfer and separation. 120 On that basis, a recent experimental study indicated that a CoCr 2 O 4 /g-C 3 N 4 heterojunction emerged for the first time and exhibited high activity for hydrogen evolution. 119 According to XPS spectra and DFT calculations (Figure 7a−c), the existence of OVs can provide abundant free electrons, which oscillated to form the LSPR effect under the excitation of light, 127 creating favorable circumstances for broadening NIR-light absorption and elaborating photogenerated charges transformation.…”
Section: Semiconductorsmentioning
confidence: 99%